EFSUMB Recommendations and Guidelines for Gastrointestinal Ultrasound - Part 1: Examination Techniques and Normal Findings (Short version) - Nylund, Kim; Maconi, Giovanni; Hollerweger, Alois; Ripolles, Tomas; Pallotta, Nadia; Higginson, Antony; Serra, Carla; Dietrich, Christoph F.; Sporea, Ioan; Saftoiu, Adrian; Dirks, Klaus; Hausken, Trygve; Calabrese, Emma; Romanini, Laura; Maaser, Christian; Nuernberg, Dieter; Gilja, Odd Helge (Ultraschall in der Medizin - European Journal of Ultrasound, 2017)
In October 2014 the European Federation of Societies for Ultrasound in Medicine and Biology formed a Gastrointestinal Ultrasound (GIUS) task force group to promote the use of GIUS in a clinical setting. One of the main objectives of the task force group was to develop clinical recommendations and guidelines for the use of GIUS under the auspices of EFSUMB. The first part, gives an overview of the examination techniques for GIUS recommended by experts in the field. It also presents the current evidence for the interpretation of normal sonoanatomical and physiological features as examined with different ultrasound modalities.
Keywords: guideline; ultrasound; gastrointestinal; examination technique; normal variants